Dragon writers : an anthology - Mangum, Lisa (WordFire Press, 2016)
"Dragons are creatures of legend ... of magic. Of wisdom, nature, and the power of creation. They have been in every culture and mythology since the beginning of time. Writers are creatures of legend ... with magic, wisdom and the power of creation at their fingertips. They, too, are in every culture and have been creating their own mythologies since the beginning of time. Within each writer is the power of a dragon ... the power of creation. Gathered together are twenty-six stories from writers who dared to tame this power, including New York times best-selling authors Brandon Sanderson, Jody Lynn Nye, Todd McCaffrey, and David Farland. Through fantasy, sci-fi, romance, and poetry, this anthology celebrates the magic and majesty of dragons, writers, and creativity. Within these pages, you'll find dragons who fly through space, who raise hatchings, who carny the power of life and death. Some dragons are even featured as swords, places, and origami creatures. Dragon writers is a special collection where magic and myth combine to create something legendary"--Page 4 of cover